2022
DOI: 10.3389/fonc.2022.917439
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Application of Radionuclide-Labeled HER2 Affibody for the Diagnosis and Treatment of Ovarian Cancer

Abstract: Human epidermal growth factor receptor 2 (HER2) is a highly expressed tumor marker in epithelial ovarian cancer, and its overexpression is considered to be a potential factor of poor prognosis. Therefore, monitoring the expression of HER2 receptor in tumor tissue provides favorable conditions for accurate localization, diagnosis, targeted therapy, and prognosis evaluation of cancer foci. Affibody has the advantages of high affinity, small molecular weight, and stable biochemical properties. The molecular probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 119 publications
1
10
0
Order By: Relevance
“…As a commonly used radionuclide for labeling SPECT imaging agents, 99m T has a half-life of 6.02 h, which can be obtained through a 99 Mo- 99m Tc generator and is inexpensive, so it is widely used in clinical and basic research. At present, due to its nonspecific uptake in the liver, gastrointestinal tract, and so on, studies that the molecular probe of 99m Tc-labeled HER2 affibody in ovarian cancer is still in the preclinical research stage [12,18]. Previous study revealed that the hydrophobicity of the HEHEHE tag can reduce the retention of the tracer in the liver [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a commonly used radionuclide for labeling SPECT imaging agents, 99m T has a half-life of 6.02 h, which can be obtained through a 99 Mo- 99m Tc generator and is inexpensive, so it is widely used in clinical and basic research. At present, due to its nonspecific uptake in the liver, gastrointestinal tract, and so on, studies that the molecular probe of 99m Tc-labeled HER2 affibody in ovarian cancer is still in the preclinical research stage [12,18]. Previous study revealed that the hydrophobicity of the HEHEHE tag can reduce the retention of the tracer in the liver [19].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, commonly used molecular imaging probes targeting HER2 include antibodies, small molecular polypeptides, or proteins that specifically bind to the receptor [2]. Affibody is a kind of scaffold protein with moderate molecular weight, which has the advantages of high affinity with the target molecule, fast clearance in vivo and easy labeling [11,12]. As a radionuclide tracer for SPECT, 99m Tc has a convenient source, low price and good nuclear physics properties, and its labeled molecular probe is suitable for SPECT imaging that is more widely carried out around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this finding may be that their larger size has more mutable sites for binding and better spatial steric resistance after binding. Fortunately, through constructing a dimer/trimer affibody or further mutating other certain residues in the affibody scaffold ( 57 ), the affinity of affibody can be further improved, and the larger size of the dimer or trimer will further improve their spatial steric resistance in the neutralizations. Otherwise, the cocktail therapy mixtures of the affibody with MAbs, or different affibodies together may be another promising strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental activities conducted in radioactive environments present varied levels of radiological hazards, depending on the kind and chemical forms of radionuclides (Table ). The chemical analysis of actinides and spent fuel reprocessing frequently involves the use of radionuclides, such as 237 Np, 243/241 Am, and 239/242 Pu, which are typical α-particle emitters with prolonged half-lives and can pose significant internal exposure risks if ingested. In addition, β-emitting radionuclides, including 90 Sr, 177 Lu, and 131 I, are typically used in therapeutic and theranostic applications. , Moreover, the radioactive decay of these radionuclides often emits γ rays with high penetrating ability .…”
Section: Radiological Hazards In a Radiochemistry Laboratorymentioning
confidence: 99%